Experimental mucositis and experimental gingivitis in persons aged 70 or over. Clinical and biological responses. Issue 8 (23rd June 2016) - Meyer, Simon; Giannopoulou, Catherine; Courvoisier, Delphine; Schimmel, Martin; Müller, Frauke; Mombelli, Andrea
Abstract: Objectives: To compare in persons aged 70 years or older the clinical and inflammatory changes occurring around implants and natural teeth during and after a phase of undisturbed plaque accumulation. Material and methods: Twenty partially edentulous participants with titanium implants refrained from oral hygiene practices while being clinically monitored in weekly intervals for 21 days. Teeth and implants were then cleaned, oral hygiene resumed, and the participants were further monitored for 3 weeks. Twelve biomarkers were assessed in gingival and peri‐implant crevicular fluid (GCF, PCF). Results: During 3 weeks of oral hygiene abstention, the gingival index (GI) continuously increased. On day 21, there were significantly more sites with GI >1 at implants than at teeth. After restarting oral hygiene, the GI decreased markedly in both groups. Throughout the experiment, the plaque index was significantly higher on teeth than on implants. The different biomarkers reacted variably. IL‐1β increased significantly with plaque accumulation. IL‐1β, GM‐CSF, TNF‐α, and IFN‐γ were significantly higher in GCF compared to PCF at day 21. IL‐8 decreased significantly in GCF up to day 14. MIP‐1β decreased significantly in GCF, but not in PCF. At the 3‐week follow‐up, the levels of all biomarkers assessed in GCF and PCF had returned to baseline values. Conclusions: In an elderly cohort, plaque accumulation induced an inflammatory reaction around both teeth and implants. Although there was less plaque accumulation on implants, the peri‐implant mucosa showed a stronger clinical response than gingiva.